2014
DOI: 10.1021/jp5079339
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Molecular Encapsulation of an ICT Fluorescence Probe in the Supramolecular Cage of Cucurbit[7]uril and β-Cyclodextrin: An Experimental and Theoretical Approach

Abstract: Supramolecular interaction between an intramolecular charge transfer (ICT) probe, N,N-dimethylaminonaphthyl-(acrylo)-nitrile (DMANAN), and two well-recognized macrocyclic hosts, cucurbit[7]uril (CB7) and β-cyclodextrin (β-CD), has been studied in aqueous medium by absorption, emission, time-resolved measurements, and (1)H NMR spectroscopic methods. The changes in the profiles of the fluorescence spectra illustrate significant modifications in fluorescence intensity, decay time, and quantum yield upon confineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The final concentrations of all organic molecules for the fluorescence experiments were micromolar levels, in line with literature reports of analogous fluorescence experimental procedures. [27] The affinities were measured using Benesi-Hildebrand fluorescence experiments, [28] and the experimental results highlighted compounds 2, 5, and 9 as excellent hosts for the benzo[a]pyrene guests (Table 3, Figure 5). [24] The differences in solvent composition and overall concentration between the fluorescence and 1 H NMR experiments are likely to lead to differences in the intermolecular interactions between the macrocycles and small-molecule guests, as these interactions are known to be strongly solvent-and concentration-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final concentrations of all organic molecules for the fluorescence experiments were micromolar levels, in line with literature reports of analogous fluorescence experimental procedures. [27] The affinities were measured using Benesi-Hildebrand fluorescence experiments, [28] and the experimental results highlighted compounds 2, 5, and 9 as excellent hosts for the benzo[a]pyrene guests (Table 3, Figure 5). [24] The differences in solvent composition and overall concentration between the fluorescence and 1 H NMR experiments are likely to lead to differences in the intermolecular interactions between the macrocycles and small-molecule guests, as these interactions are known to be strongly solvent-and concentration-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these measured differences in supramolecular complexation as a result of changes in the solvent and concentration provide important information about the intermolecular forces responsible for such complexation, and the extent to which hydrophobic interactions (promoted in the mostly aqueous solvent system) lead to and support ternary complex formation. [27] The affinities were measured using Benesi-Hildebrand fluorescence experiments, [28] and the experimental results highlighted compounds 2, 5, and 9 as excellent hosts for the benzo[a]pyrene guests (Table 3, Figure 5). Other macrocycle hosts either displayed poor linear fits in the Benesi-Hildebrand plots (indicating little to no binding of benzo[a]pyrene in the macrocycle cavity), lower calculated association constants (indicated weaker binding of benzo[a]pyrene in the macrocycle cavity), or marked decreases in the fluorescence of the benzo[a]pyrene upon increasing the concentration of the macrocycle host (for compounds 7, 8, and 10).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been partly attributed to the deep inclusion of the pyrazoline fragment into the CD cavity ( Fig. 5.4), thereby restricting the rotational and vibrational motions of NPCP and hence inhibiting the occurrence of nonradiative decay processes [81]. Under the stoichiometry of 1:1, the association constant K for NPCP/γ-CD complexes (1.3 3 10 4 mM 21 ) has been reported to be much higher than that of NPCP/β-CD complexes (5.8 3 10 3 mM 21 ).…”
Section: Manipulation Of Hostàguest Complexationmentioning
confidence: 99%
“…[8,45] Interestingly, Guchhait and Bhattacharya showed that complex 22.CB [7] presents a dual exponential anisotropy decay. [55] Those rotational correlation times would return reasonable, albeit large hydrodynamic radii (5.3 and 11 Å , respectively), assuming that the viscosity inside CB [7] is similar to bulk water, a very questionable hypothesis! [55] Those rotational correlation times would return reasonable, albeit large hydrodynamic radii (5.3 and 11 Å , respectively), assuming that the viscosity inside CB [7] is similar to bulk water, a very questionable hypothesis!…”
Section: Kinetics Of Guest Motion Inside Cucurbiturilsmentioning
confidence: 99%